THE RHETORICAL MODEL OF ENGLISH SALES COPIES POSTED ON INSTAGRAM - Warsidi, Warsidi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
In this internet era, the issue of market globalization has led and encouraged both individual and cooperative businesses to improve their creativity for selling products widely. However, studies that underpin this essential issue in linguistic concerns are still limited. Studies on the rhetorical structure of English sales copies, for example, have been rarely conducted, while investigating this fundamental issue is urgently conducted to improve product sales globally. In responding to this urgent need, I investigated the rhetorical model of English sales copies. Data in this study are 30 English sales copies posted on Instagram. These data were collected by three students taking a course in creative writing. For the analysis, I employed genre-based analysis using a top-down approach. The analysis discovered a rhetorical model that fitted the rhetorical structures of the present data set. The model contained three important functional moves, namely establishing a positive impression, establishing customers’ interest, and facilitating the purchasing process. To realize these functional moves, copywriters employed some possible strategies. Compared to earlier literature, the present finding has differences from those found in literature, on the one hand, but similarities, on the other hand. For example, establishing customers’ interest, and facilitating the purchasing process are obligatory, while establishing a positive impression is conventional in the present study.